Forms of support to the caregiver of people in home care: scope review protocol (Research, Society and Development, 2022)
Objective: map the forms of support organization for home caregivers of functionally dependent people in Brazil and in other countries. Methodology: Scope Review Protocol, carried out according to methodological recommendations from the Joanna Briggs Institute (JBI) and the PRISMA Extension for Scoping Reviews checklist (PRISMA-ScR), in order to answer the research question “what are the forms of support organization for home caregivers of functionally dependent people in Brazil and in other countries?” elaborated according to the acronym PCC (Population; Concept; Context), where P refers to home caregivers, C forms of support organization and C home, home care. The information sources will be: international and national databases, repositories, theses and dissertations database, institutional sources, references found in selected articles. Three search steps will be developed using the terms “home care services”, “caregiver” and “social support”: 1) in databases; 2) in theses and dissertations repositories; 3) in institutional documents. In addition to step 1, references to the references of the articles selected for the composition of the analysis material will be identified.